2002
DOI: 10.1046/j.1523-1755.2002.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma aminothiol oxidation in chronic hemodialysis patients

Abstract: Plasma aminothiols are excessively oxidized in uremia, while the hemodialysis procedure is restorative of redox status. Oxidized aminothiols are candidate uremic toxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 59 publications
3
51
0
3
Order By: Relevance
“…[57] Several experimental studies have shown that antioxidant capacity of tissues is decreased in animals with CRF, [58,59] while marked reductions in plasma glutathione concentration and glutathione peroxidase activity, as well as marked increases in the ratios of oxidized to reduced GSH were observed in CRF patients. [60,61] Current findings show that the reduction in GSH content of the studied tissues of male and ovariectomized rats may be due to its consumption during CRF-induced oxidative stress. On the other hand, administration of E 2 , through its antioxidant properties and by inhibiting lipid peroxidation, maintained the glutathione levels and thereby protected the tissues against oxidative stress.…”
Section: Discussionmentioning
confidence: 91%
“…[57] Several experimental studies have shown that antioxidant capacity of tissues is decreased in animals with CRF, [58,59] while marked reductions in plasma glutathione concentration and glutathione peroxidase activity, as well as marked increases in the ratios of oxidized to reduced GSH were observed in CRF patients. [60,61] Current findings show that the reduction in GSH content of the studied tissues of male and ovariectomized rats may be due to its consumption during CRF-induced oxidative stress. On the other hand, administration of E 2 , through its antioxidant properties and by inhibiting lipid peroxidation, maintained the glutathione levels and thereby protected the tissues against oxidative stress.…”
Section: Discussionmentioning
confidence: 91%
“…Fourth, previous data from our group and others have suggested that oxidation of thiol groups, particularly in plasma proteins, is especially prominent in persons with kidney disease. 29,30 Finally, we hypothesized that combining predominantly lipophilic antioxidants (tocopherols) with more water-soluble antioxidants (ALA) would provide synergistic antioxidant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that low-molecular-weight thiols and plasma protein thiols are markedly oxidized in patients undergoing MHD. 29,30 In a prospective randomized clinical trial, administration of the thiol-containing antioxidant N-acetylcysteine markedly decreased the cardiovascular event rate in a cohort of MHD patients, suggesting potential utility for this approach. 31 a-Lipoic acid (ALA) is a thiol-containing antioxidant that can replete reduced thiol groups, restore intracellular glutathione levels, and participate in the redox recycling of ascorbate and tocopherols.…”
mentioning
confidence: 99%
“…5 It is interesting to note that patients with chronic renal failure also develop evidence for systemic inflammation and oxidant stress. 26,27 Oxidant stress is believed to be a major pathogenic factor in the cardiovascular disease seen in renal failure, 31 as well as the general population. 32 The concept that hormonal adaptations to decreases in renal function might participate in the pathogenesis of the uremic syndrome was elaborated in the 1960s.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we found that animals subjected to partial nephrectomy developed systemic oxidant stress along with alterations of diastolic function quite consistent with that seen in patients afflicted with chronic renal failure. 31,34 This was not very surprising, because the rat partial nephrectomy model has been extensively studied as a model for chronic renal failure. 4 Next, we saw that infusion of 10 g/kg per day of MBG, which produces levels comparable to those in partial nephrectomy rats, produced almost identical increases in the plasma level of MBG to that seen with partial nephrectomy.…”
Section: Discussionmentioning
confidence: 99%